Sense of space: Tactile sense for exploratory behavior of roots - Ken Yokawa; František Baluška (Communicative & Integrative Biology, 2018)
In soil, plant roots grow in heterogeneous environments. Plant roots are always facing the difficulty of searching effectively the patchy natural resources, such as water, oxygen, ions and mineral nutrition. Numerous studies reported that root apex navigation enables roots to explore complex environments. In this short communication, we characterize how growing maize roots explore narrow space available with two experimental settings: tactile exploration of narrow glass tube and circumnutation in free space. We also discuss root growth in the soil in terms of foraging behavior guided by the sensory root apex.